Selection of optimal conductor set and application to radial network topology - Yap, Kerwin Thomas L.
A utility's power distribution system can become a very considerable expense and reducing this cost becomes a primary concern for distribution planning. The selection of the appropriate conductors for design and upgrade show itself to be a very influential factor in the cost of a distribution system. Every conductor has unique characteristics and can be the most economical for a particular loading range. With this in mind, utilities must find the most economical set of conductors to cover a desired loading range that meet their requirements. This project will present a systematic method for selecting the optimal conductor set from a universal set of conductors for equal weights of loading ranges. It also aims to be able to theoretically implement the conductor set to a given topology assuming a balanced system and to determine the conductor size per segment. The conductor databases used consists of seven types of conductors. These conductors are AC35, AC50, AC70, AC95, AC120, AC150 and AC185 in single-phase and three-phase.